2008
DOI: 10.1055/s-0028-1112116
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Intramedullary Teratomas

Abstract: Teratomas account for 3% of all childhood tumors, with the majority occurring in the sacrococcygeal region and in the ovary. Intradural spinal teratomas are extremely rare dysembryogenetic tumors. Spinal cord teratomas may be extradural, intradural or intramedullary. Intramedullary ones are the least frequently seen. We have extensively reviewed the literature for intramedullary spinal cord teratomas in children. Although an intramedullary teratoma of the conus medullaris in children is a rare entity, it shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…10,14,45 Resection is the initial step in the management for IMSCTs followed by adjuvant therapy in some cases. 5,13,15,16,18,33 …”
mentioning
confidence: 99%
“…10,14,45 Resection is the initial step in the management for IMSCTs followed by adjuvant therapy in some cases. 5,13,15,16,18,33 …”
mentioning
confidence: 99%
“…5,11 Teratomas comprise 3% of all pediatric tumors and 0.1% of all CNS tumors. 8 Only 0.2%-0.5% of CNS terato- mas occur in the spinal cord. 13 In a recent review, Işik et al 8 identified 16 reported cases of intramedullary teratomas in children.…”
Section: Discussionmentioning
confidence: 99%
“…8 Only 0.2%-0.5% of CNS terato- mas occur in the spinal cord. 13 In a recent review, Işik et al 8 identified 16 reported cases of intramedullary teratomas in children. Of these, only 1 was designated as "immature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, teratomas of the central nervous system (CNS) are especially rare and account for only 0.1% of all CNS tumors 6. Spinal cord teratomas are even rarer and can be present in extradural, intradural, or intramedullary locations 7.…”
Section: Introductionmentioning
confidence: 99%